2018
DOI: 10.2478/humo-2013-0028
|View full text |Cite
|
Sign up to set email alerts
|

Methods of determining hip joint centre: their influence on the 3-D kinematics of the hip and knee during the fencing lunge

Abstract: Purpose. The lunge is a fundamental offensive fencing technique, common to all contemporary fencing styles. Therefore, when using 3-D kinematic analysis to quantify lower extremity rotations during the fencing lunge, it is important for researchers to correctly interpret this movement. Locating the centre of the hip is required to accurately quantify hip and knee joint rotations, with three non-invasive techniques using anatomical, functional and projection methods currently available for the estimation of hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…However, in the coronal and transverse planes, significant differences were mediated as a function of the four HJC location techniques. These observations concur with those of Sinclair et al (2013) who showed that non-sagittal parameters were significantly influenced as a function of different HJC location methods. It should be noted that the functional HJC configuration was shown to be habitually different from the other methods used in this study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, in the coronal and transverse planes, significant differences were mediated as a function of the four HJC location techniques. These observations concur with those of Sinclair et al (2013) who showed that non-sagittal parameters were significantly influenced as a function of different HJC location methods. It should be noted that the functional HJC configuration was shown to be habitually different from the other methods used in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Means and standard deviations from the 3-D kinetic and kinematic parameters were calculated for each hip joint centre location technique. Differences between the parameters were examined using one-way repeated measures ANOVA with significance accepted at the p ≤ 0.05 level ( Sinclair et al, 2013 ). Post-hoc pairwise comparisons were conducted on all significant main effects using a Bonferroni adjustment to control type I error.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being the most common attack with all three fencing weapons, a powerful lunge is fundamental to successful performance [11,20]. Papers describing lunge technique mention the fact that the foot moves forward prior to the armed hand performing the movement [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have focused their studies on the kinematic profile of the movements in fencing (Bober et al, 2017;Bottoms et al, 2013;Geil, 2002;Gholipour et al, 2008;Sillero et al, 2008;Sinclair & Bottoms, 2013a, 2013bStewart & Kopetka, 2005). The summarizing review of the studies focused on fencing movements was done by Chen et al (2017).…”
Section: Introductionmentioning
confidence: 99%